1990
DOI: 10.1152/ajplung.1990.259.6.l372
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical removal of airway epithelium disrupts mast cells and releases granules

Abstract: Many previous investigators have utilized mechanical rubbing as a method for examining effects of epithelial removal. In the present study, we examined whether this procedure also affects mast cell integrity in the underlying lamina propria. We isolated bronchial rings from six ferrets, and we found that removal of epithelium by rubbing decreased the total number of intact mast cells from 10.0 +/- 1.9 to 2.2 +/- 0.6 (SE) mast cells/mm luminal perimeter (P less than 0.01). In addition, we found a very large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Several studies have previously reported such an inflammatory response within the airway mucosa and fewer reports have provided ultrastructural data. [1][2][3][4][5][6][7] Until recently, however, the study of inflammation was limited to the submucosa whereas the airway smooth muscle (ASM) was strictly considered as an effector that contracts and/or proliferates in response to inflammatory cell products.…”
mentioning
confidence: 99%
“…Several studies have previously reported such an inflammatory response within the airway mucosa and fewer reports have provided ultrastructural data. [1][2][3][4][5][6][7] Until recently, however, the study of inflammation was limited to the submucosa whereas the airway smooth muscle (ASM) was strictly considered as an effector that contracts and/or proliferates in response to inflammatory cell products.…”
mentioning
confidence: 99%
“…Murlas reported that the removal of the epithelium augmented the contractions evoked by EFS and histamine, but not those produced by potassium and ACh [25]. However, mechanical removal of the epithelium may alter the contractility of smooth muscle by mechanisms that are independent of the epithelial cell, such as the activation of mast cells [14]. The present findings indicate that products of the epithelial cells are responsible for inhibiting cholinergic neurotransmission.…”
Section: Discussionmentioning
confidence: 42%
“…In control experiments lower S2/S1 ratios were obtained in mucosa-denuded than in mucosa-intact tracheae (see Table 1 and 3), indicating some fading of evoked [3H]-acetylcholine release in the former. It had been shown that mechanical removal of the mucosa, as applied in the present study, disrupts mast cells and causes release of their content (Franconi et al, 1990)…”
Section: Discussionmentioning
confidence: 63%